Honey bee colony winter loss rates for 35 countries participating in the COLOSS survey for winter 2018–2019, and the effects of a new queen on the risk of colony winter loss - Gray, Alison; Adjlane, Noureddine; Arab, Alireza; Ballis, Alexis; Brusbardis, Valters; Charrière, Jean-Daniel; Chlebo, Robert; Coffey, Mary F.; Cornelissen, Bram; Amaro da Costa, Cristina; Dahle, Bjørn; Danihlík, Jiří; et al. (Informa UK Limited, 2020)
This article presents managed honey bee colony loss rates over winter 2018/19 resulting from using the standardised COLOSS questionnaire in 35 countries (31 in Europe). In total, 28,629 beekeepers supplying valid loss data wintered738,233 colonies, and reported 29,912 (4.1%, 95% confidence interval (CI) 4.0–4.1%) colonies with unsolvable queen problems, 79,146 (10.7%, 95% CI 10.5–10.9%) dead colonies after winter and 13,895 colonies (1.9%, 95% CI 1.8–2.0%)lost through natural disaster. This gave an overall colony winter loss rate of 16.7% (95% CI 16.4–16.9%), varying greatly between countries, from 5.8% to 32.0%. We modelled the risk of loss as a dead/empty colony or from unresolvablequeen problems, and found that, overall, larger beekeeping operations with more than 150 colonies experienced significantly lower losses (p < 0.001), consistent with earlier studies. Additionally, beekeepers included in this survey who didcnot migrate their colonies at least once in 2018 had significantly lower losses than those migrating (p < 0.001). The percentage of new queens from 2018 in wintered colonies was also examined as a potential risk factor. The percentage ofcolonies going into winter with a new queen was estimated as 55.0% over all countries. Higher percentages of youngcqueens corresponded to lower overall losses (excluding losses from natural disaster), but also lower losses from unre-solvable queen problems, and lower losses from winter mortality (p < 0.001). Detailed results for each country andcoverall are given in a table, and a map shows relative risks of winter loss at regional level.
Keywords: Apis mellifera; mortality; colony winter losses; queens; queen replacement; monitoring surveys; beekeeping; citizen science